2014
DOI: 10.1371/journal.pone.0095838
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Antimicrobial Activity of Culturable Endophytic Fungi Isolated from Moso Bamboo Seeds

Abstract: Bamboos, regarded as therapeutic agents in ethnomedicine, have been used to inhibit inflammation and enhance natural immunity for a long time in Asia, and there are many bamboo associated fungi with medical and edible value. In the present study, a total of 350 fungal strains were isolated from the uncommon moso bamboo (Phyllostachys edulis) seeds for the first time. The molecular diversity of these endophytic fungi was investigated and bioactive compound producers were screened for the first time. All the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Both bacteria activated Hypoxia‐inducible factor 1‐alpha (HIF‐1α), which is a regulator of innate immunity and cathelicidin LL‐37 (an antimicrobial peptide) to oppose C albicans colonisation . Commensal bacteria triggered a host response to oppose C albicans colonisation . In a preclinical study using a mice model, the use of S cerevisiae CNCM I‐3856 strain helped prevent adherent‐invasive Escherichia coli (AIEC) from adhering to an inflamed intestinal mucosa, resulting in the amelioration of colitis …”
Section: Interaction Between Gut Fungi and Other Microbial Kingdoms Imentioning
confidence: 99%
See 1 more Smart Citation
“…Both bacteria activated Hypoxia‐inducible factor 1‐alpha (HIF‐1α), which is a regulator of innate immunity and cathelicidin LL‐37 (an antimicrobial peptide) to oppose C albicans colonisation . Commensal bacteria triggered a host response to oppose C albicans colonisation . In a preclinical study using a mice model, the use of S cerevisiae CNCM I‐3856 strain helped prevent adherent‐invasive Escherichia coli (AIEC) from adhering to an inflamed intestinal mucosa, resulting in the amelioration of colitis …”
Section: Interaction Between Gut Fungi and Other Microbial Kingdoms Imentioning
confidence: 99%
“…103 colonisation. 33,105 In a preclinical study using a mice model, the use of S cerevisiae CNCM I-3856 strain helped prevent adherentinvasive Escherichia coli (AIEC) from adhering to an inflamed intestinal mucosa, resulting in the amelioration of colitis. 106…”
Section: Competition Between Bacteria and Fungimentioning
confidence: 99%
“…Lorenz Hiltner defined the term "rhizosphere" in 1904 [15], and plant-associated microorganisms with root systems have received substantial attention in recent years [13,14,16]. Moso bamboo-associated bacteria and fungi have been isolated using culture-dependent methods [17,18] and high-throughput sequencing [19], but the latter study was primarily focused on the bamboo rhizome and pole-bacterial communities. The leaves of plants are ubiquitous global habitats that are inhabited by a diverse community of microorganisms [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in the literature have reported that rhizospheric microorganisms, especially rhizobacteria, show excellent results in promoting plant growth (Ahemad and Kibret, 2014;Lugtenberg and Kamilova, 2009;Myresiotis et al, 2014;Prashar et al, 2014). Another extensively studied group is the endophytic microorganisms, similar to the rhizobacteria, with the potential for use in various other economic crops (Brader et al, 2014;Hallmann et al, 1997;Rosenblueth and Martinez Romero, 2006;Shen et al, 2014). Yeasts are unicellular fungi that can also be found in the rhizosphere of plants, but in smaller numbers compared to bacteria and filamentous fungi; however, little information is known about their function in this ecosystem.…”
Section: Introductionmentioning
confidence: 99%